Transport infrastructure in Italian public expenditure - Cerrone, Daniela (TeMA - Journal of Land Use, Mobility and Environment, 2008)
It’s quite a long time that the need is felt for an integrated approach to the territory-mobility system; an approach allowing to plan, programme and carry out interventions affecting urban and territorial development. An approach targeted to point out strategies being more effective and consistent with the goals of competitive growth. In order to assess the effects that a more integrated territory-mobility approach could produce in relation to the functional reorganization of urban systems both on national and local scale, the paper suggests an analysis that quantifies the “financial mass” invested in transport infrastructure and urban equipments as well as its weight modification in the course of time. The above said assessment was worked out by analysing the trend of public expenditure in Italy during the five-year period 2000-2005, appraising the “value” of the interventions in transport infrastructure in comparison to the interventions for realizing and managing urban equipments. The worked out analysis stresses how much the strategies of territorial development, both on central and local level, mainly rely on the interventions for realizing and managing transport infrastructures. Therefore, a new approach could better address the great deal of resources (58% of expenditure for public works amounting to over €150.000) that regards the sector of transport infrastructures, although the trend context shows a great reduction of public financial resources destined to expenditure policies.